Molecular evolution of the porcine type I interferon family: subtype-specific expression and antiviral activity - Sang, Yongming; Bergkamp, Joseph; Blecha, Frank (My University, 2015)
Type I interferons (IFNs), key antiviral cytokines, evolve to adapt with ever-changing viral threats during vertebrate speciation. Due to novel pathogenic pressure associated with Suidae speciation and domestication, porcine IFNs evolutionarily engender both molecular and functional diversification, which have not been well addressed in pigs, an important livestock species and animal model for biomedical sciences. Annotation of current swine genome assembly Sscrofa10.2 reveals 57 functional genes and 16 pseudogenes of type I IFNs. Subfamilies of multiple IFNA, IFNW and porcine-specific IFND genes are separated into four clusters with ~60 kb intervals within the IFNB/IFNE bordered region in SSC1, and each cluster contains mingled subtypes of IFNA, IFNW and IFND. Further curation of the 57 functional IFN genes indicates that they include 18 potential artifactual duplicates. We performed phylogenetic construction as well as analyses of gene duplication/conversion and natural selection and showed that porcine type I IFN genes have been undergoing active diversification through both gene duplication and conversion. Extensive analyses of the non-coding sequences proximal to all IFN coding regions identified several genomic repetitive elements significantly associated with different IFN subtypes. Family-wide studies further revealed their molecular diversity with respect to differential expression and restrictive activity on the resurgence of a porcine endogenous retrovirus. Based on predicted 3-D structures of representative animal IFNs and inferred activity, we categorized the general functional propensity underlying the structure-activity relationship. Evidence indicates gene expansion of porcine type I IFNs. Genomic repetitive elements that associated with IFN subtypes may serve as molecular signatures of respective IFN subtypes and genomic mechanisms to mediate IFN gene evolution and expression. In summary, the porcine type I IFN profile has been phylogenetically defined family-wide and linked to diverse expression and antiviral activity, which is important information for further biological studies across the porcine type I IFN family.
Keywords: Type I interferons; Pigs